Potret Konformitas dalam Kelompok Remaja Laki-Laki Urban Komunitas BC - Ditha Prasanti; Sri Seti Indriani (Universitas Ahmad Dahlan, 2020)
This article is a research study on communication behavior, especially regarding group conformity and communication motives that occur in urban adolescents. The BC community is a unique urban teenage boy community as a group of young people who are digitally literate and prioritize the value of conformity in their group. Therefore, the author wants to describe the conformity and motives of adolescents in the community. This study uses the Schutz phenomenology method because it observes the communication behavior of the study of group conformity and male adolescent motives. The results of the research showed that the conformity of the group in the BC community was formed due to personal factors and situational factors; The motives underlying the male adolescent communication behavior in the BC community are classified into because of motives and to motives. In the end, the writer found that conformity and motive are two different things but inherent in the individual so that the author can see what trends will be done by male adolescents. This is an impact arising from the conformity and motives they have.